2018
DOI: 10.1051/matecconf/201815902034
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Sensors for Real-time Monitoring and Control Systems on Machining and Surface Finishing Processes

Abstract: One of the key components in real-time monitoring and control on machining and surface finishing processes are sensors. The advances of such system have triggered interesting questions on sensor selection that act as the fundamental before starting a project. This paper is made to review and answer the questions surrounding sensor selection. The paper first explains on the type of sensors commonly used in practice for real-time monitoring and control systems. After which, the paper discusses on how often the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The literature review of sensors selection which is reported in [2] narrows down 7 types of sensor suitable for monitoring, namely acoustic emission (AE) sensor, accelerometer, force sensor, dynamometer, proximity sensor, thermometer, and strain gauge. The first four sensors are more common to be used than the last three.…”
Section: Sensor and Data Acquisitionmentioning
confidence: 99%
See 2 more Smart Citations
“…The literature review of sensors selection which is reported in [2] narrows down 7 types of sensor suitable for monitoring, namely acoustic emission (AE) sensor, accelerometer, force sensor, dynamometer, proximity sensor, thermometer, and strain gauge. The first four sensors are more common to be used than the last three.…”
Section: Sensor and Data Acquisitionmentioning
confidence: 99%
“…The grading is concluded based on extensive reading and comparison on various papers done in different surface finishing processes. The study for the grading can be found in the paper reported in [2]. Grading of each sensors type is stated in Fig.…”
Section: Sensor and Data Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Correlation between tool vibration based on contact conditions can be used to verify the state of the tool during grinding. AE, force and accelerometer sensors show greater sensitivity at ultra-precision machining regime which is a typical characteristic of any abrasive machining process [46,47]. Complimentary multi-sensor integration system incorporating force, accelerometer and AE has been proposed as a strategy to estimate the values of physical variables being measured to give a complete picture of the tool condition state of abrasive belt grinding process which is difficult to understand.…”
Section: Complementary Based Multi-sensor Integration Systemmentioning
confidence: 99%